Limited book loan facility during peak hours - Jaafar, Ahmad Faizar; Jantan, Azizi; Jaafar, Ahmad Nazri; Kosnan, Ja'amayah; Sulaiman, Muhamad Azmir; Mohd Salleh, Abdul Hamid; Mohamad, Rosli; Yazid Yahaya, Mohd; Mohd Radwan, Rizana (2010)
Library offers library loan process by two methods. First to the counter. Both can deal in books vending machine. However , this loan facility through the machine has only one unit in the library.